2017
DOI: 10.1061/(asce)wr.1943-5452.0000827
|View full text |Cite
|
Sign up to set email alerts
|

Development and Implementation of an Optimization Model for Hydropower and Total Dissolved Gas in the Mid-Columbia River System

Abstract: Managing energy, water, and environmental priorities and constraints within a cascade hydropower system is a challenging multiobjective optimization effort that requires advanced modeling and forecasting tools. Within the mid-Columbia River system, there is currently a lack of specific solutions for predicting how coordinated operational decisions can mitigate the impacts of total dissolved gas (TDG) supersaturation while satisfying multiple additional policy and hydropower generation objectives. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Previous studies have shown that gas bubble disease (GBD) induced by TDG plays a role in decreasing the survival of fish inhabiting the lower reaches of dams [6]. TDG supersaturation occurred downstream of some hydropower structures in the Columbia River basin due to flood discharge in the spill season and caused the death of chum salmon [7][8][9]. Similar circumstances were also found downstream of the Cabinet Gorge Dam in the Clark Fork River [10].…”
Section: Introductionmentioning
confidence: 73%
“…Previous studies have shown that gas bubble disease (GBD) induced by TDG plays a role in decreasing the survival of fish inhabiting the lower reaches of dams [6]. TDG supersaturation occurred downstream of some hydropower structures in the Columbia River basin due to flood discharge in the spill season and caused the death of chum salmon [7][8][9]. Similar circumstances were also found downstream of the Cabinet Gorge Dam in the Clark Fork River [10].…”
Section: Introductionmentioning
confidence: 73%
“…The influence of TDG supersaturation on river ecosystems has become an ecological environmental issue of global concern [8,9,10]. Endemic fish in the Columbia River of the United States suffered mortality caused by TDG supersaturation when hydropower structures discharged flows during the flood season [11,12,13]. Similar phenomena were also found downstream of the Danube River [14].…”
Section: Introductionmentioning
confidence: 94%
“…With respect to the TDG change in air that occurs in Stage 1, the TDG level in the spilling jet when the jet enters the stilling basin is always assumed to be 100% (Li et al 2009). According to the results of field measurements, high TDG levels often occur in forebays due to the cumulative effects of cascade hydropower stations (Qu et al 2011;Witt et al 2017a). To determine whether the forebay TDG level has an impact on the production of elevated TDG levels, Ma (2016) conducted a series of experiments to investigate the relationship between the TDG level and conditions of jets when they enter stilling basins.…”
Section: Analysis Of Tdg Generation Processesmentioning
confidence: 99%